2022
DOI: 10.3389/fneur.2021.822342
|View full text |Cite
|
Sign up to set email alerts
|

Telestroke for the Treatment of Ischemic Stroke in Western China During the COVID-19 Pandemic: A Multicenter Observational Study

Abstract: BackgroundIntravenous thrombolysis is still underutilized in patients with acute ischemic stroke (AIS) in China. A promising strategy for addressing this issue, especially in situations, such as the global pandemic of coronavirus disease 2019 (COVID-19), is the telestroke mode, which remains to be widely implemented in China. The present study aimed to assess the effects of telemedicine for patients with stroke in Western China, as well as the impact of the pandemic on telestroke services in 1 year after the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The other explanation may includes the quick respon to transport patients to the ward in pandemic situation with overcrowded emergency department, the protected stroke code, as well as a greater experience of local telestroke team (Sevilis, et al 2022). The reason for this also added by Chen, et al (2022), by stated that it was due to lower total number of patients in most hospitals and smoother access to investigations and treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other explanation may includes the quick respon to transport patients to the ward in pandemic situation with overcrowded emergency department, the protected stroke code, as well as a greater experience of local telestroke team (Sevilis, et al 2022). The reason for this also added by Chen, et al (2022), by stated that it was due to lower total number of patients in most hospitals and smoother access to investigations and treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothetically, the use of technologybase healthcare services, such as telehealth, would likely elevate during the pandemic period due to the social distancing and stay at home regulation that promote to reduce the spread of the virus. The application of telestroke have been proven to be effective to care stroke patient as well as to promote, evaluate and manage the disease, and rehabilitate related to stroke (Chen, 2022). In the contrary, this has been reported that the request for telestroke admission is decreased significantly after WHO declared this pandemic situation.…”
Section: Introductionmentioning
confidence: 99%
“…One pandemic-era report from the Spanish region of Catalonia showed that their 14 TS centers experienced more than 30% reduction in TS code activations and > 50% decrease in thrombolysis treatment in the first 7 weeks following the declaration of the pandemic compared to the 7-week period pre-pandemic [53]. However, reports from western China and Chile each showed that their TS systems and networks did not face any significant reduction in stroke codes or reperfusion therapy in the first year of the pandemic compared to the year before [55,56].…”
Section: Global Impact Of Covid-19 On Telestrokementioning
confidence: 99%
“… 63 Using telemedicine was also effective in improving the thrombolysis administration during the COVID-19 pandemic among Chinese patients who had limited access to hospitals. 64 Current studies worldwide and in WPR during the COVID-19 pandemic showed that the screening and management of CMDs based on dHealth techniques would be efficient ways to guide the high-risk population to carry out lifestyle self-management, non-drug treatments, or medication measurements through remote approaches. By using these techniques, the frequency and duration of hospital visits for CMDs management were largely decreased, and the exposure risk of COVID-19 was also substantially reduced.…”
Section: Applications Of Dhealth Regarding Cmds In the Context Of Cov...mentioning
confidence: 99%